La Evaluación Diagnóstica Integral Y Las Estrategias De Enseñanzas A Los Estudiantes Del Nivel De Básica Superior De La Unidad Educativa “León De Febres Cordero” De La Parroquia San Juan, Cantón Puebloviejo, Provincia De Los Ríos. - Paucar Vecilla Segundo Washington (2015)
The comprehensive diagnostic evaluation is a systematic process that verifies the cognitive, psychological and relational family member of a student conditions, the results are a starting point for educational planning. Currently in educational institutions, teachers generally applied instruments diagnostic evaluation only knowledge, obtaining results that do not give importance, and perform their curricular instruments with new knowledge of the current course and emerge a no-number of drawbacks because they did not consider the palpable reality of the student's comprehensive education. The situation presented in the educational context guided me to investigate the student comprehensive diagnostic evaluation, considering the importance of this information in educational planning Knowing learning styles, personality factors of influence, etc. Furthermore this thesis provides a guide to implementing comprehensive diagnostic assessment that will be very useful to teachers.